Desapariciones forzadas en América Latina y México: evolución del fenómeno y rol del crimen organizado - Aureliani, Thomas (El Colegio de México A.C., 2023)
The severe crisis of insecurity and human rights in contemporary Mexico demands from academia a profound analysis of the phenomenon of organized crime, informed by international experiences and sensitive to its dual nature as a phenomenon with deep local roots that is, simultaneously, inseparable from the flows of the global economy. Against this backdrop, in March 2023, the seminar “Dialogues from the Frontiers of Organized Crime: Organized Crime, Rights, and Educational Poverty” was held at El Colegio de México, in collaboration with the University of Milan, the Embassy of Italy in Mexico, the Pontifical International Marian Academy, the Mexican Institute for Justice, and the Memory and Tolerance Museum. During the seminar, scholars, analysts, and officials examined the penetration of organized crime into the political, social, and economic life of Mexico and other Latin American countries, with special attention to the parallels and lessons that can be drawn from the Italian experience. In Italy, as in Mexico today, the historical intertwining of crime with economic and social relations has confronted the state, political elites, and civil society with the need to initiate extraordinary processes of memory, truth, justice, and institutional reconstruction. Due to the significance of the topic and the introduction of analytical perspectives useful for studying criminal dynamics and its implications, we reproduce three presentations from the seminar. In the first, Nando dalla Chiesa, a prominent sociologist, intellectual, professor at the University of Milan, and emblematic figure of the Italian anti-mafia movement, outlines three approaches to the study of criminal dynamics at the international level. These approaches include the process of multiplication of criminal organizations on a global scale, the proliferation of mercenary armies and paramilitary forces, and the growing interconnection between crime and political terrorism. Dalla Chiesa also reflects on the difficulties in distinguishing criminal activity from the rest of economic and social interaction. Phenomena like money laundering increasingly blur the boundaries between society and crime, formal and informal economy, businesspeople and criminals, legality and illegality. In the second presentation, Annaclara De Tuglie reflects on the levels of analysis in the study of organized crime, ranging from a “macro” perspective that addresses the geopolitical and transnational components of the phenomenon (such as migration, capital flows to tax havens, among others) to the “micro” level, which focuses on individual and local experiences in dealing with crime and the conditions that facilitate its reproduction. Finally, leveraging the analytical tools discussed in the other presentations, Thomas Aureliani provides an overview of the phenomenon of forced disappearances in Mexico, based on his own fieldwork and testimonies from family members of victims of a crime that starkly reflects the crisis of stateness and human rights overshadowing the country.